An Exploratory Analysis of Proprotein Convertase Subtilisin/Kexin Type 9 Inhibition and Aortic Stenosis in the FOURIER Trial - Bergmark, Brian A; O'Donoghue, Michelle L; Murphy, Sabina A; Kuder, Julia F; Ezhov, Marat V; Ceška, Richard; Gouni-Berthold, Ioanna; Jensen, Henrik K; Tokgozoglu, S Lale; Mach, François; Huber, Kurt; Gaciong, Zbigniew; et al. (JAMA cardiology, 2020)
Importance: Despite recent advances in treatment of severe aortic valve stenosis (AS), AS remains a life-threatening condition with no proven disease-modifying therapy. Low-density lipoprotein cholesterol (LDL-C) and lipoprotein(a) (Lp[a]) have been implicated in the pathobiology of AS. The proprotein convertase subtilisin/kexin type 9 inhibitor evolocumab reduces circulating LDL-C concentrations by 50% to 60% and Lp(a) by 20% to 30%. Objective: To determine whether evolocumab reduces the risk of AS events in patients with atherosclerotic cardiovascular disease. Interventions: Patients were randomized 1:1 to evolocumab or placebo. Design, Setting, and Participants: Exploratory analysis of the FOURIER trial, which enrolled 27 564 patients with stable atherosclerotic cardiovascular disease who were taking statin therapy at 1242 sites in 49 countries from February 2013 to November 2016. Patients were randomized to evolocumab or placebo and followed up for a median (interquartile range) of 2.2 (1.8-2.5) years. This post hoc analysis was performed from September 2019 to February 2020. Main Outcomes and Measures: Site-reported adverse events of new or worsening AS or aortic valve replacement (termed AS events). The adjusted risk of AS events was calculated with a multivariable model including concentrations of Lp(a) and LDL-C corrected for Lp(a) content, plus age, sex, diabetes, hypertension, current smoking, and estimated glomerular filtration rate. Evolocumab efficacy was tested using a Cox proportional hazards model. Results: Aortic stenosis events occurred in 63 patients (48 men [76%]; mean [SD] age, 69 [9] years) over a median of 2.2 years. Elevated Lp(a) concentration was associated with higher rates of AS events (adjusted hazard ratio [aHR], 1.55 [95% CI, 1.17-2.05] per SD; P = .002), including aortic valve replacement (aHR, 2.22 [95% CI, 1.38-3.58] per SD; P = .001), after multivariable adjustment. The corrected LDL-C concentration was not significantly associated with AS events (aHR, 1.23 [95% CI, 0.93-1.61] per SD; P = .14). The overall HR for AS events with evolocumab was 0.66 (95% CI, 0.40-1.09), with no apparent association in the first year (HR, 1.09 [95% CI, 0.48-2.47]) but an HR of 0.48 (95% CI, 0.25-0.93) after the first year of treatment. Conclusions and Relevance: In this exploratory analysis of the FOURIER trial, higher Lp(a) levels, but not Lp(a)-corrected LDL-C levels, were associated with a higher risk of subsequent AS events, including aortic valve replacement. Long-term therapy with evolocumab may reduce AS events, and this raises the possibility that specific pharmacologic lipid-lowering therapy could offer a means to prevent or slow the progression of AS. These exploratory findings merit further investigation with a dedicated randomized clinical trial. Trial Registration: ClinicalTrials.gov Identifier: NCT01764633.
Keywords: rizikové faktory; Male; Female; Subtilisin; humanizované monoklonální protilátky; Middle Aged; Treatment Outcome; subtilisin; LDL-cholesterol; Anticholesteremic Agents; mužské pohlaví; Cholesterol, LDL; ženské pohlaví; Risk Factors; PCSK9 inhibitory; Proprotein Convertase 9; proproteinkonvertasa subtilisin/kexin typu 9; anticholesteremika; PCSK9 Inhibitors; lidé středního věku; aortální stenóza; výsledek terapie; Aortic Valve Stenosis; lidé; Humans; Antibodies, Monoclonal, Humanized